The Effect of Increased Intraocular Pressure During Steep Trendelenburg Positioning in Robotic Prostatectomy and Hysterectomy on Structural and Functional Ocular Parameters. (April 2020) - Awad, Hamdy; Bai, Michael; Ramadan, Mohamed Ehab; Shabsigh, Ahmad; Backes, Floor; Craven, Mary Abigail; Abdel-Rasoul, Mahmoud; Bergese, Sergio D.; Slabaugh, Mark
Abstract : BACKGROUND: Robotic prostatectomy and robotic hysterectomy require steep Trendelenburg positioning. Many authors documented significant increases in intraocular pressure (IOP) during steep Trendelenburg. However, the long-term biological effect of a significant increase in IOP on the structural and functional ocular system is unknown. This study examines the effect of a significant increase in IOP on the visual acuity, retinal nerve fiber layer thickness (RNFLT), and ganglion cell complex (GCC) thickness in 52 patients without preexisting ocular disease of both genders before and 3 months after their procedures. METHODS: This was a prospective cohort study. The total number of patients included was 56, then 3 females and 1 male case were excluded, totaling 28 robotic hysterectomies and 24 robotic prostatectomies were performed. Patients underwent complete eye examination before the procedure and 3 months after, measuring the main outcome of RNFLT and the secondary outcomes of GCC thickness, foveal threshold (FT), mean deviation (MD), and pattern standard deviation (PSD). These outcomes were analyzed using linear mixed-effects models. On the day of surgery, we examined the IOP after induction of anesthesia, at the end of steep Trendelenburg, and in the recovery room. RESULTS: There were significant differences in IOP values at the end of steep Trendelenburg versus after induction and 45–60 minutes post-awakening ( P < .001 for both groups). No difference between IOP 45 and 60 minutes post-awakening and IOP after induction was observed in either group. The highest IOPs occurred at the end of the steep Trendelenburg time point for both groups. The mean duration of steep Trendelenburg in robotic prostatectomy was 184.6 minutes (standard deviation [SD] = 30.8), while the mean duration in robotic hysterectomy was 123.0 minutes (SD = 29.8). All ophthalmologic examinations were normal preoperatively and 3 months postoperatively. The ocular parameters in the retina and optic disk did not differ significantly before surgery and 3 months after. CONCLUSIONS: There is a significant increase in IOP during steep Trendelenburg positioning. There was no significant difference in the ocular parameters examined 3 months after the procedure in this cohort.